The Concept of Investment in Iraqi Law (Comparative Study) - Mahmood, Ammar Shakir (Journal of Economic, Administrative and Legal Sciences, 2020)
Investment is of paramount importance at the moment as it is the most effective means of advancing economic and social development and thus contributes to the development of countries and the well-being of peoples, whether directly or indirectly. This provided an incentive for countries to compete and compete with each other to attract investment by providing the appropriate legal framework to achieve an optimal investment environment. The success of this approach depends on the extent to which the legislator understands the concept of investment and clarifies its concept clearly and flexibly to accommodate all future investment activities., And to clarify the impact on the investment process to ultimately reach a specific concept of investment.